Repeated treatment with gefitinib and alectinib in a patient with multiple EGFR-mutant and ALK-mutant lung adenocarcinomas: A case report. (2021) - Yorozuya, Takafumi; Nagano, Yutaro; Chiba, Hirofumi; Imai, Yui; Yasuda, Kento; Sudo, Yuta; Taya, Tetsuya; Shioya, Makoto
Abstract: Multiple EGFR-mutant and ALK-mutant lung cancers are rare, and standard treatment has not been established because of the small number of cases. A 79-year-old man was found to harbor nodular shadows in right S1, right S5, and left S3. He was surgically diagnosed with stage IIB (pT3N0M0) EGFR G719X-mutant lung adenocarcinoma in left S3 and stage IA1 (pT1aN0M0) ALK-mutant lung adenocarcinoma in right S5. Owing to the relapse of the EGFR-mutant adenocarcinoma, gefitinib treatment was commenced 3 months postoperatively. The tumor shrank temporarily; however, the nodular shadow in the right S1 and #3a lymph nodes were found to increase in size. He was diagnosed with adenosquamous carcinoma in right S1 and relapsing ALK-mutant adenocarcinoma in #3a lymph node. Gefitinib treatment was continued, but due to a renewed increase in the size of the #3a lymph node, the drug was changed to alectinib 16 months postoperatively. Subsequently, the EGFR-mutant adenocarcinomas were found to increase in left S1 despite the decrease in the #3a lymph node size. Nineteen months after the first surgery, the treatment was changed to gefitinib, and repeated treatment with this drug and alectinib administered every 2 months was continued. This approach enabled 39 months of progression-free survival, and no serious adverse events were observed. Highlights: Few treatment cases for EGFR- and ALK-mutant lung cancers have been reported. It might be impossible to control tumors with EGFR-TKI or ALK-TKI alone. Repeated treatment with gefitinib and alectinib showed a good response. No serious adverse events were observed with this treatment.